2010
DOI: 10.1007/s10528-010-9390-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships Among 22 Taxa of Bamboo Revealed by ISSR and EST-Based Random Primers

Abstract: Genetic relationships among 22 taxa of bamboo were evaluated using 12 inter simple sequence repeats (ISSR) and four expressed sequence tag (EST)-based random primers, resulting in amplification of 220 loci. The grouping of species based on Jaccard's similarity matrix using UPGMA and principal coordinate analysis agreed with earlier published reports on molecular phylogenetic studies in bamboos with few deviations. In the dendrogram, however, species of one genus were placed in different clusters along with mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…22 But, Incidence of flowering of woody bamboo is uncertain. 23,24 As reported earlier, the reproductive cycle of bamboo is too long from 3years to 120years. 25 That is why the identification depending on reproductive structure is difficult.…”
Section: Discussionmentioning
confidence: 84%
“…22 But, Incidence of flowering of woody bamboo is uncertain. 23,24 As reported earlier, the reproductive cycle of bamboo is too long from 3years to 120years. 25 That is why the identification depending on reproductive structure is difficult.…”
Section: Discussionmentioning
confidence: 84%
“…Bamboo has age-old connection with the material needs of rural people (Mukherjee et al 2010 ). Porter-field ( 1933 ) suggested that “bamboo is one of those providential developments in nature which, like the horse, the cow, wheat and cotton, have been indirectly responsible for man’s own evolution”.…”
Section: Introductionmentioning
confidence: 99%
“…In case of gregarious flowering, all the members of a common cohort (plants from seeds of common origin) go into reproductive phase simultaneously and subsequently die (Bhattacharya et al 2009 ). Incidence of flowering of woody bamboo is uncertain (Ramanayake et al 2007 ; Mukherjee et al 2010 ). As reported earlier, the reproductive cycle of bamboo is too long, from 3 to 120 years (Janzen 1976 ), hence making the identification depending on reproductive structure difficult (Bhattacharya et al 2006 , 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis is the first study investigating the genetic diversity and structure of K. debilis from Sri Lanka, with samples from almost all known populations evaluated using microsatellite markers. Although several studies have previously quantified population level genetic variation in bamboos, none of them have related this variation to the conservation of bamboo populations or species (Nayak et al, 2003;Ramanayake et al, 2007;Lalhruaitluanga & Prasad, 2009;Mukherjee et al, 2010;.…”
Section: Conservation Implicationsmentioning
confidence: 99%